Single Cell Analysis Contemporary Research and Clinical Applications - Robinson, J. Paul.; Cossarizza, Andrea; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book highlights the current state of the art in single cell analysis, an area that involves many fields of science - from clinical hematology, functional analysis and drug screening, to platelet and microparticle analysis, marine biology and fundamental cancer research. This book brings together an eclectic group of current applications, all of which have a significant impact on our current state of knowledge. The authors of these chapters are all pioneering researchers in the field of single cell analysis. The book will not only appeal to those readers more focused on clinical applications, but also those interested in highly technical aspects of the technologies. All of the technologies identified utilize unique applications of photon detection systems.
Microenvironment Cytometry -- High Throughput and High Content Flow Cytometry -- E all'ottavo giorno, Dio creò la citometria (and on the 8th day, God created Cytometry...) -- The immunology of Aging -- Stem Cells: Current knowledge -- Advances in T cell biology -- Cytomic Analysis of Oxidative Stress -- Cancer Stem Cells and Multi-Drug Resistance by Flow Cytometry -- Molecular understanding of the control of immune reactions and immunological memory in vaccination -- Dynamics of memory plasma cell niches -- Heterogeneity of tumor-infiltrating leukocytes: implications for adoptive cell transfer immunotherapy -- Can We Find Disease Mechanisms by Studying Healthy Individuals -- The Next Dimensions in Single Cell Cytometry -- RNA Flow Cytometry -- Adapting the economy to aging: evidence from biological processes -- Assessing immunological aging using flow cytometry -- Host-microbe interaction at mucosal surfaces.
Keywords: Biomedical engineering; Immunology; Biophysics; Cancer; Cytology; Biomedical Engineering and Bioengineering; Immunology; Biophysics; Cancer Biology; Cell Biology